Influence of integrated nutrient management and high density multi-species cropping system on soil properties, plant nutrition and yield in root (wilt) affected coconut palms - H.P. Maheswarappa; P. Anitha Kumari; P.G. Kamalakshiamma; M. Shanavas (International Coconut Community, 2005)
A field experiment was conducted at Central Plantation Crops Research Institute (Regional Station), Kayamkulam, Kerala, India to study the effect of integrated nutrient management and high density multi-species cropping system in root (wilt) affected garden on root (wilt) index, yield of coconut palms and soil properties. The experimental results indicated that, there was improvement in soil properties like water holding capacity, organic carbon, major and micronutrient status of the soil due to adoption of integrated nutrient management practices and high density multi-species cropping system. There was improvement in the yield of the palms under different root (wilt) diseased palms coupled with reduction in root (wilt) indices due to reduction in root (wilt) symptoms especially yellowing. The increase in nut yield (five years average) was to the tune of 54.5%, 52%, 48.3% and 40.9% under apparently healthy, disease early, disease middle and disease advanced palms in comparison with pre-experimental yield.